Positioning of Women’s cooperative action in Province of Essaouira - OULAHCEN, Zakaria; Elharmouzi, Nouh (Revue du contrôle, de la comptabilité et de l’audit, 2024)
The entrepreneurial labor of feminine agricultural cooperatives, like the one in question here, in the province of Essaouira, Morocco, has apparently somewhat departed from its territorial objective. What leads us to write this article is our wish to understand the reasons behind this deviation. The overall goal of this study is to follow the setting up of a cooperative action venture for a well-positioned business governance and cooperative action. The feminine cooperatives in Essaouira have yet to position themselves as the market dictates because their marketing presence is not adequately developed. As a consequence, their social economy is lacking and cooperative action in the province requires a truly rational revision. Field work was carried out to gather qualitative data according to a precise systemic analysis from a sample of one hundred agricultural cooperatives established in the province of Essaouira. At the end of the article we will offer suggestions as to an effective support for members of the cooperatives and entrepreneurs so that their labor may follow a sound business ethic.